Towards the measurement of food literacy with respect to healthy eating: the development and validation of the self perceived food literacy scale among an adult sample in the Netherlands - Maartje P. Poelman; S. Coosje Dijkstra; Hanne Sponselee; Carlijn B. M. Kamphuis; Marieke C. E. Battjes-Fries; Marleen Gillebaart; Jacob C. Seidell (BMC, 2018)
Abstract Background Food literacy refers to the capability to make healthy food choices in different contexts, settings and situations. The aim of this study is to develop and validate the self-perceived food literacy (SPFL) scale, to assess individuals' level of food literacy, including a knowledge, skills and behavior to plan, manage, select, prepare and eat food healthfully. Methods An initial set of 50 items for the SPFL scale were generated based on expert insights and literature. A cross-sectional online survey was conducted among a sample of Dutch adults (n = 755) in order to determine convergent, divergent and criterion validation against psychosocial variables that were expected to correlate with food literacy (self-control, impulsiveness) and against the expected outcome of high food literacy, namely healthy food consumption. Principal Component Analyses (PCA), Pearson correlation tests and linear regression analyses were conducted. The capacity to distinguish of the SPFL scale was determined by comparing SPFL scores of the general population with that of a sample of dieticians (n = 207). Results The participants in the general sample had an average age of 44.8 (SD:16.1), the majority were women (90.7%), they had a healthy weight (61.4%) and were highly educated (59.1%). Of the initial 50 items, 29 items remained after PCA and reflected eight domains of food literacy. SPFL was positively correlated with self-control (r = 0.51, p = <.001) and negatively with impulsiveness (r = − 0.31, p = <.01). Participants with higher levels of food literacy reported a significantly higher frequency of fruit consumption (≥5 times/week), vegetable consumption (≥5times/week) and fish consumption (≥1times/week) and consumed larger portions of fruit (≥2pieces/day) and vegetables ≥200 g/day) in comparison with participants who had lower levels of food literacy. Dieticians had slightly higher scores on SPFL than general adults (B = 0.08, SE = 0.03, t = 2.83, 95%-CI = 0.03 to 0.14). Conclusions The 29 item SPFL scale is a validated, expert-based and theory-driven tool for measuring self-perceived food literacy with respect to healthy eating among adults. Higher levels of food literacy were associated with more self-control, less impulsiveness and healthier food consumption. Additional research is needed to validate the SPFL scale in different populations (different age groups, socioeconomic groups, male populations) and in different contexts.